Teaching performance and evaluation of educational quality in the “Manuel Scorza Torre 8161” Educational Institution. Carabayllo. Lima - Romero Rodríguez , Rosmery (2024)
One of the valuable topics in the achievement of student learning is to investigate the relationship that exists between teaching performance and its relationship with educational quality, and that is the objective of this study. For this purpose, a scientific study with a quantitative approach, hypothetical deductive method, cross-sectional, ordinal level, was carried out on 40 teachers from IE N.8161 Manuel Scorza Torres de Carabayllo in Lima. with a descriptive correlational non-experimental design. In data collection we used the survey through two questionnaires on teaching performance and educational quality in the EI in question. The instruments were validated through judgment by 3 experts and reliability by the Crombach coefficient. The results are obtained through descriptive and inferential statistics to contrast hypotheses and establish the evaluation between the variables under study. The inferential analysis by Spearman's Rho statistician allows us to obtain r= ,521  and p=,001  less than the decision sigma 0.05, we conclude that there is a moderate significant relationship between the teaching performance variable and educational quality in our study. As long as there is good teaching performance, greater educational quality is guaranteed at the IE. The dimensions were statistically analyzed: preparation for learning, teaching for learning, participation in school and community management and professionalization and teacher identity.